Estudio de factibilidad para la creación de un Buffet de Servicios Jurídicos Prepagados para la ciudad de Loja - Mogrovejo León, Laura Cecilia (2015)
The present work has as main objective of this work was: Prepare a Draft Feasibility for a feasibility study for the creation of a Buffet Prepaid Legal Services for the City of Loja which corresponds to an idea or business initiative that has certain phases service, marketing, planning and evaluation for the implementation of that company. To this have been taken into account a set of resources, human, material, technological and others that allowed establishing whether the project is viable or not. With the use of deductive, analytical, mathematical and statistical methods and by applying the techniques of observation and survey, it was possible to conduct different studies containing this project as they are Market Research, Technical Study, Organizational Study and Financial Study. The market is segmented Study Population Loja according to the 2010 Census was 180,617 inhabitants and projected to 2015 with a growth rate of 2.65% for a total of 186,908 inhabitants, the PEA is 53.2%, which equals 99435 PEA to the Canton Loja. With a total of 382 surveys, then giving the results to quantify unmet demand for services in the year 95 001. The technical study, determined that the company will have an installed production capacity of 12,480 services a year, according to the calculations is estimated to be able to receive 13.13% of the unmet demand for care in the market starting with seating capacity used 92% for the first year of the project; for effect materials, equipment, machinery, supplies and human resources required for service in the city of Loja are listed. Subsequently, the legal structure of the company, in which fundamental in the operation hierarchical levels and good organization of the company, which is detailed as a limited liability company whose corporate name will LEX Cia defined is designed Ltda. The Economic and Financial Study identified that the areas of investment needed for the implementation of the project are Fixed Assets, and Deferred Assets Current assets so you have a total investment of $ 84,309.80 dollars. Financial evaluation determined the project's viability by the financial indicators: Getting a positive NPV 93,887.83; R (B / C) of 1.31 dollars; PRC in 2 years, 9 months and 29 days; with an IRR of 34.67% higher than the opportunity cost of capital of 12% and a sensitivity of 0.99 with increased costs and decreased 16.13% from 12.34% revenue they finally came to the conclusions and recommendations which is due to translate this study.